Factors Affecting Transformation of Pasteurella novicida - Tyeryar, Franklin J. (1970)
The requirements and characteristics of Pasteurella novicida transformations in liquid suspensions were studied. Transformation frequencies of 0.1 to 0.3% were routinely obtained when recipient cells were harvested from 16-hr agar plates and higher than 1% when logarithmic-phase broth-grown cells were used. Calcium ions were essential for transformations. The deoxyribonucleic acid dose response curve, kinetics of transformation, and pH optimum for transformations were similar to those of other bacterial transformation systems. The genetic relatedness of P. novicida and P. tularensis was established by transforming P. novicida mutants with deoxyribonucleic acid extracted from P. tularensis.